2023
DOI: 10.1136/bmjpo-2023-001934
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postreperfusion syndrome during living donor liver transplantation in paediatric patients with biliary atresia: a retrospective analysis

Abstract: BackgroundLiving donor liver transplantation (LT) is the main treatment for paediatric biliary atresia (BA) in Asia. During LT, a series of haemodynamic changes often occur during LT reperfusion, which is called postreperfusion syndrome (PRS), and PRS is related to a prolonged postoperative hospital stay, delayed recovery of graft function and increased mortality. To reduce adverse reactions after paediatric living donor LT (LDLT), our study’s objectives were to ascertain the incidence of PRS and analyse possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…In addition, Lauterio et al [ 7 ] recently showed that CIT >6 h and >10 h were associated with graft failure in a cohort of in-situ PSLT. Besides, CIT is related to PRS [ 12 ] and IRI which are known risk factors for graft loss [ 13 ]. HOPE has been shown to improve graft preservation by actively oxygenating the graft associated with shorter CIT [ 8 ], translating into decreased PRS [ 10 , 25 , 26 ], decreased EAD, ischemic type biliary complications and graft loss [ 11 ] in adult LT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Lauterio et al [ 7 ] recently showed that CIT >6 h and >10 h were associated with graft failure in a cohort of in-situ PSLT. Besides, CIT is related to PRS [ 12 ] and IRI which are known risk factors for graft loss [ 13 ]. HOPE has been shown to improve graft preservation by actively oxygenating the graft associated with shorter CIT [ 8 ], translating into decreased PRS [ 10 , 25 , 26 ], decreased EAD, ischemic type biliary complications and graft loss [ 11 ] in adult LT.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, meaningful statistical adjustments for recipient risk factors were not possible due to the small sample size. Nevertheless, early IRI events such as PRS [ 12 , 13 ] and IRI on reperfusion biopsy [ 30 ] have been shown to significantly impact long-term post-LT outcomes in larger cohorts, including LDLT [ 12 ] and serve as early surrogates of graft quality.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Gordon et al [ 1 ] study did not include all events that had an impact on prognosis in regression analysis, such as postreperfusion syndrome (PRS). PRS is defined as a significant decrease of over 30% in the mean arterial pressure compared with that at the end of the anhepatic phase, and this decrease has to last at least 1 minute and occur in the first 5 min after liver graft reperfusion[ 7 ]. Decreased body temperature in children before reperfusion and prolonged graft cold ischemia time are independent risk factors for PRS in pediatric liver transplantation[ 7 ].…”
Section: To the Editormentioning
confidence: 99%
“…PRS is defined as a significant decrease of over 30% in the mean arterial pressure compared with that at the end of the anhepatic phase, and this decrease has to last at least 1 minute and occur in the first 5 min after liver graft reperfusion[ 7 ]. Decreased body temperature in children before reperfusion and prolonged graft cold ischemia time are independent risk factors for PRS in pediatric liver transplantation[ 7 ]. Metabolic acidosis, hyperkalemia, hypocalcemia, and the release of many proinflammatory cytokines into the systemic circulation by the transplanted liver releasing after reperfusion are possible mechanisms for PRS[ 8 ].…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation